Cosmos caudatus Leaf Ethanol Extract Inhibit Growth and Viability through Membrane Permeability and Apoptosis in Candida albicans - Agustina Tri Endharti (Journal of Global Pharma Technology, 2019)
Objective: Candidiasis is the most common fungal gynecological disease in humans. Essentially, the use of antifungal such as Fluconazole has reportedly increased resistance to candidiasis by 7%. The flavonoid has been shown to be used as an antifungal in Candida albicans. Cosmos caudatus contains 51% of Quercetin. To prove the influence of the use of flavonoid antifungal of quercetin group on the growth, viability, membrane permeability, and apoptosis of the C. albicans. Methods: The SV-1148 coded C. albicans isolate was obtained from the Microbiology Laboratory of Brawijaya University, Malang, Indonesia. Initially, the isolate was grown in Sabouraud Dextrose Agar (SDA) medium. The samples were divided into negative and positive control groups of fluconazole (60µg/ml) and difference concentrations (5%, 10%, 20%, and 40%) of leaves ethanol extract of C. caudatus. Results:  Concentration of 40% ethanol extract C. caudatus has Minimum Inhibitory Concentration (MIC) of 30%. This result showed that 40% ethanol extract C. caudatus was able to provide the best growth resistance which was characterized by the absence of colonies from C. albicans. The data of Influx Assay Iodide increased membrane permeability of C. albicans to disrupt cell membranes and induce apoptosis. The percentage of apoptosis increased after treatment of 40% ethanol extract C. caudatus in the culture of C. albicans. Conclusion: C. caudatus has antifungal activity and can be used as an herbal drug in C. albicans infection.